“Comparison of Cochlear Microphonics Magnitude with Broad and Narrow Band Stimuli in Healthy Adult Wistar Rats” - Heidari, Fatemeh; Pourbakht, Akram; Kamrava, Seyed Kamran; Kamali, Mohammad; Yousefi, Abbas (Iranian Journal of Child Neurology, 2018)
Abstract Objective: Cochlear microphonic (CM) is a cochlear AC electric field, recorded within, around, and remote from its sources. Nowadays it can contribute to the differential diagnosis of different auditory pathologies such as auditory neuropathy spectrum disorder (ANSD). The aim of this study was to compare CM waveforms (CMWs) and amplitudes with broad and narrow band stimuli in 25 healthy male young adult Wistar rats. Methods: Using an extratympanic technique in ECochG (Electrocochleography) recording, CMWs in response to click and tonal stimuli with different octave frequencies were recorded at a high intensity level in subjects. The CMW amplitudes were calculated by a graphical user interface (GUI) designed in MATLAB. The data was analyzed by One-way ANOVA test. Results: The CMW magnitude increased upon an increase in band width stimulation. Across tonal stimuli, the CMW amplitudes at lower frequency tones were larger than those at higher frequency tones. Those findings were statistically significant (P< 0.001). Conclusion: This study found that CMW most likely is a reflection of spatial summation of voltage drops generated by hair cell groups in response to acoustic stimulation. In order to production nature of CM potentials as well as their very small magnitudes especially with tonal stimuli, thus, we recommend using click stimulation for CM potential recording especially in patient with ANSD that CM plays an important role in its differential diagnosis and follow up